Facile tuning of strong near-IR absorption wavelengths in manganese(iii) phthalocyanines via axial ligand exchange. Issue 47 (7th May 2019) - McKearney, Declan; Zhou, Wen; Zellman, Carson; Williams, Vance E.; Leznoff, Daniel B.
Abstract : We report two series of manganese(iii ) phthalocyanines that possess intense, narrow absorptions tunable from 815 to 948 nm via simple axial ligand exchange on the metal centre, making them attractive as near-IR absorbing and emitting materials. Abstract : The facile tuning of near-infrared absorption of manganese(iii ) phthalocyanines was accomplished by changing the nature and number of bound axial ligands. For a series of axial ligands on manganese α-octabutoxyphthalocyanine and α-octakis-(isopropylthio)phthalocyanine, the electron density on the metal and its displacement from the Pc-ring plane both control the position of the complex's Q-band. For these two macrocycles, this strong absorption band could be tuned over a λ max range of 815–948 nm by axial ligand exchange.